Pyogenic Granuloma with Calcification: An Enigmatic Case - Satinderpal Kaur; Deepti Garg; Swati Gautam; Nishat Sankhyan (Dental Journal of Advance Studies)
Oral mucosa is one of the most common sites for reactive lesions as it is exposed to various internal and external stimuli. Pyogenic granuloma (PG) and peripheral ossifying fibroma (POF) are the most common reactive lesions associated with gingiva. Both lesions have similar clinical features and can be differentiated based on histopathology only. Pyogenic granuloma is a type of benign swelling and type of inflammatory hyperplasia that results in response to chronic irritation, trauma, and fluctuating hormones. Microscopically, ossification is a feature of POF and it is not seen in PG. This article aims to discuss the histopathology of PG in a young 18-year-old female patient, in which areas of ossification were seen that are not commonly encountered in this lesion.